MEDIA PERMAINAN TEBAK GAMBAR EFEKTIF DALAM PENINGKATAN PENGETAHUAN DAN TINDAKAN MENYIKAT GIGI DIBANDINGKAN MEDIA BOOKLET - Diyah Fatmasari; Agustina Purba; Salikun Salikun (Jurnal Kesehatan Gigi, 2019)
The high number of dental and oral diseases is influenced by the main factors,  lack of knowledge about oral hygiene and poor diet. Information about dental health and dental care can be obtained from various media both print media and electronic media. Purpose of this study was to determine the effectiveness of booklet media and picture guessing games to increase knowledge and actions of brushing teeth for students at Padangsari 02 Elementary School Semarang. Study design  is a quasi-experimental design with a pre and post test group with two group design. The population of the researchers is students in grades 4 and 5 at Padangsari 02 Elementary School Semarang. Samples were taken by purposive sampling as many as 50 students, divided into two groups, namely 25 students in the booklet group and 25 students in the guessing game group. The data obtained are analyze using Wilcoxon-test and Mann-Whitney test. There was a significance differences with value of p = 0,000 between knowledge and action before and after of both groups. ,The Mann-Whitney Test showed difference in effectiveness between the two media. Game guess images is more effective than booklet with mean rank of    game guess images and booklte was 29.27 and 24.25.